2011
DOI: 10.3390/ijms12128581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conjugated Linoleic Acid, Fish Oil and Soybean Oil on PPARs (α & γ) mRNA Expression in Broiler Chickens and Their Relation to Body Fat Deposits

Abstract: An experiment was conducted on broiler chickens to study the effects of different dietary fats (Conjugated linoleic acid (CLA), fish oil, soybean oil, or their mixtures, as well as palm oil, as a more saturated fat), with a as fed dose of 7% for single fat and 3.5 + 3.5% for the mixtures, on Peroxisome Proliferator-Activated Receptors (PPARs) gene expression and its relation with body fat deposits. The CLA used in this experiment was CLA LUTA60 which contained 60% CLA, so 7% and 3.5% dietary inclusions of CLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 72 publications
3
23
0
Order By: Relevance
“…On the other hand, Suksombat et al (2007) reported that the reduced abdominal fat pad in birds fed dietary CLA was not accompanied by any increase in carcass, breast or thigh composition. Royan et al (2011a) confirmed the reduction in abdominal fat by a downregulation of PPAR-γ mRNA expression in the abdominal adipose tissue. The PPAR-γ is the most important transcription factor which regulates lipid metabolism and adipocyte differentiation, and is strongly associated with the abdominal fat deposition in avian species (Sato et al, 2009;Xiong et al, 2010).…”
Section: Effects Of Cla On Poultry Lipid Metabolismsupporting
confidence: 78%
“…On the other hand, Suksombat et al (2007) reported that the reduced abdominal fat pad in birds fed dietary CLA was not accompanied by any increase in carcass, breast or thigh composition. Royan et al (2011a) confirmed the reduction in abdominal fat by a downregulation of PPAR-γ mRNA expression in the abdominal adipose tissue. The PPAR-γ is the most important transcription factor which regulates lipid metabolism and adipocyte differentiation, and is strongly associated with the abdominal fat deposition in avian species (Sato et al, 2009;Xiong et al, 2010).…”
Section: Effects Of Cla On Poultry Lipid Metabolismsupporting
confidence: 78%
“…In numerous explorations of IMF deposition, the most obvious characterization is upregulated peroxisome proliferator activated receptor γ (PPAR γ ) abundance . Pioglitazone hydrochloride (PGZ), a high‐affinity ligand of PPAR γ , therefore interested us .…”
Section: Introductionmentioning
confidence: 99%
“…In numerous explorations of IMF deposition, the most obvious characterization is upregulated peroxisome proliferator activated receptor (PPAR ) abundance. 5,6 Pioglitazone hydrochloride (PGZ), a high-affinity ligand of PPAR , therefore interested us. 7 In studies of ruminants, intramuscular adipose deposition has already been demonstrated to be increased by dietary supplementation with PGZ.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being an important macronutrient, dietary fat has recently gained much prominence for its role in regulating gene expression in poultry (Royan et al 2011;Zhang et al 2011;Jing et al 2013). LPIN1, LPIN2, WDTC1/ADIPOSE, and △-6 fatty acid desaturase (FADS2) were reported as lipid metabolism genes in human and mouse.…”
Section: Introductionmentioning
confidence: 99%